From mechanosensing to immune regulation: mechanisms of acupuncture signal initiation and amplification mediated by macrophages - Sheng, Wenru; Wang, Rui; Xue, Xiqing; Zhao, Pan; Zhang, Jingwen; Tseng, Yiider (Frontiers in Immunology, 2026)
The core mechanism of acupuncture therapy lies in converting local mechanical stimulation into systemic physiological regulatory effects. Building on this concept, this review highlights the central role of macrophages in this mechanotransduction event, mainly occurring in the acupoint(s). During acupuncture, the practitioner’s manipulation techniques, such as lifting-thrusting and twisting, cause significant mechanical stress at an acupoint through the entanglement and traction of collagen fibers through the acupuncture needle. This physical signal is transmitted through the extracellular matrix (ECM) and delivered to the mechanosensitive cells, such as fibroblasts and macrophages. Concurrently, while fibroblasts receive the mechanical stimuli, they also release alarmin proteins, such as interleukin-33 (IL-33), to further regulate macrophages’ activities. As a key mechanical sensing and effect unit, macrophages perceive mechanical signals through multiple pathways, including Piezo1, transient receptor potential vanilloid 4 (TRPV4) mechanically sensitive channels, the integrin family of mechanotransduction receptors, and podosomes on the cell body. These pathways promptly initiate intracellular Ca2 fluctuations and promote the Yes−associated protein (YAP) and transcriptional co−activator with PDZ−binding motif (TAZ) for their nuclear translocation, as well as induce other mechanisms, generating a cascade reaction to activate macrophages. After activation, macrophages effectively recruit neutrophils and monocytes by coordinating the chemokine network and dominate the resolution of inflammation and the initiation of tissue repair via dynamic polarization between M1 and M2 phenotypes. Additionally, they regulate T cell-mediated adaptive immune responses through antigen presentation and other means, and collaborate with fibroblasts to promote the remodeling and repair of the ECM. This article focuses on providing a systematic perspective on the cellular and molecular basis of acupuncture initiation through the response of macrophages to acupuncture signals and their regulation of the immune network.